2006
DOI: 10.1097/01.ico.0000230324.28956.77
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Day and Night Wear on Surface Properties of Silicone Hydrogel Contact Lenses and Bacterial Adhesion

Abstract: In this study, the differences in surface properties between 2 types of S-H lenses were found to change after 1 week of continuous wear. Generally, bacteria adhered in lower numbers and less tenaciously to worn lenses, except S. aureus 835, adhering in higher numbers to worn balafilcon A lenses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
25
1
2

Year Published

2007
2007
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 24 publications
3
25
1
2
Order By: Relevance
“…Results are contradictory in the literature. Indeed, after continuous wear, mostly during the 1st week, it has been shown that surface properties changed, resulting in an increase of wettability due to deposits of lipids and proteins, thus decreasing the risk of bacterial adhesion for continuous wear of silicone-hydrogel lenses [41]. But it has also been demonstrated that P. aeruginosa tend to adhere more to worn contact lenses than unworn lenses [42].…”
Section: Discussionmentioning
confidence: 98%
“…Results are contradictory in the literature. Indeed, after continuous wear, mostly during the 1st week, it has been shown that surface properties changed, resulting in an increase of wettability due to deposits of lipids and proteins, thus decreasing the risk of bacterial adhesion for continuous wear of silicone-hydrogel lenses [41]. But it has also been demonstrated that P. aeruginosa tend to adhere more to worn contact lenses than unworn lenses [42].…”
Section: Discussionmentioning
confidence: 98%
“…Os microrganismos se aderem melhor em superfícies hidrofóbicas do que em superfícies hidrofílicas (3,5,22) . A presença de macromoléculas no filme lacrimal age sobre a superfície das LC, deixando-a mais hidrofílica.…”
Section: Discussionunclassified
“…A complicação mais temida é a ceratite infecciosa, que pode culminar em perfuração, cicatriz e perda permanente da visão (2) . Os principais agentes etiológicos das ceratites infecciosas em usuários de LC são Pseudomonas aeruginosa, Staphylococcus aureus e Staphyloccocus epidermidis (3)(4)(5) .…”
Section: Resumo Introduçãounclassified
“…The avoidance of protein denaturation would likely maintain any antimicrobial effect. Studies examining the effects of deposited tear film proteins have not reported a strong correlation between amount of protein deposited and adverse responses 23 or consistent effects on bacterial adhesion; [24][25][26] however, no study has yet tested the possible correlation between the presence of native protein and positive clinical effects or between denatured protein levels and adverse events.…”
mentioning
confidence: 99%